2015
DOI: 10.1145/2687924
|View full text |Cite
|
Sign up to set email alerts
|

Measurable Decision Making with GSR and Pupillary Analysis for Intelligent User Interface

Abstract: This article presents a framework of adaptive, measurable decision making for Multiple Attribute Decision Making (MADM) by varying decision factors in their types, numbers, and values. Under this framework, decision making is measured using physiological sensors such as Galvanic Skin Response (GSR) and eyetracking while users are subjected to varying decision quality and difficulty levels. Following this quantifiable decision making, users are allowed to refine several decision factors in order to make decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 41 publications
(49 reference statements)
1
22
0
Order By: Relevance
“…Galvanic Skin Response (GSR) is a physiological signal captured easily and cost effectively via the skin [15]. These signals reflect changes in the skin's ability to conduct electricity and are used to indicate the extent of nerve responses [7].…”
Section: Introductionmentioning
confidence: 99%
“…Galvanic Skin Response (GSR) is a physiological signal captured easily and cost effectively via the skin [15]. These signals reflect changes in the skin's ability to conduct electricity and are used to indicate the extent of nerve responses [7].…”
Section: Introductionmentioning
confidence: 99%
“…Such investigation could help develop more effective user interface for ML-based intelligent systems. Our previous research found that the type, number, and values of decision factors from ML output affect decision difficulties as well as decision qualities [10]. This paper is a natural extension of previous research.…”
Section: Introductionmentioning
confidence: 53%
“…In addition, Jiang, Atkins, Tien, Bednarik, and Zheng, (2014), Weber et al (2015), and Zhou et al (2015) also investigated mental effort based on pupillary responses using realistic experimental setups. Jiang et al (2014) found a relationship between pupil dilations and the level of task requirements (n = 12) in a surgical tele-operation setting.…”
Section: Pupillary Responses As a Marker Of Mental Effort In Is Researchmentioning
confidence: 99%
“…Weber et al (2015) applied a pupillary-based mental effort assessment to assess individuals when creating process models (n = 3). Zhou et al (2015) used an experimental travelroute decision making setup with 40 participants to demonstrate that one can classify subjective decision difficulty levels ex post by jointly using three task time-based factors (task time length, number of responses of pupil diameter signal, and sum of duration of pupil diameter signal).…”
Section: Pupillary Responses As a Marker Of Mental Effort In Is Researchmentioning
confidence: 99%